The right coronary artery originating from the distal circumflex artery - Songül Cuglan; Bilal Cuglan (National Scientific Medical Center, 2019)
We report a case of anomalous origin of the right coronary artery in a 58-year-old male patient. The patient had a single coronary ostium originating from the left sinus valsalva. Right coronary artery was originating from the distal circumflex artery. There was no other cardiac anomaly in association with this rare case. Our patient had only severe atherosclerosis in the proximal left anterior descending artery with normal coronary flow in the circumflex artery. Generally, cases with single coronary ostium are considered to be benign. However, these patients experience the symptoms of coronary artery disease more critically because of dependence on one coronary artery.